2010
DOI: 10.4314/mmj.v21i4.49639
|View full text |Cite
|
Sign up to set email alerts
|

Open tibia fractures in HIV positive patients

Abstract: Open tibia fractures are common injuries, particularly in developing countries.Pedestrian or bicycle to motor car contact is the most common mechanism.These injuries result in high morbidity and often long-term disability.HIV infection complicates open fractures by raising the incidence of infectionin the open wound (5 of 7 patients in our series). This risk may be compounded if internal fixation techniques are used (5 of 12 HIV patients with internal fixation of any open fracture). There is also a suggestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Likewise, HIV infection has been shown to increase the risk of infection and may alter the ultimate decision regarding type and timing of soft tissue and bone fixation [ 135 ].…”
Section: Patient Factorsmentioning
confidence: 99%
“…Likewise, HIV infection has been shown to increase the risk of infection and may alter the ultimate decision regarding type and timing of soft tissue and bone fixation [ 135 ].…”
Section: Patient Factorsmentioning
confidence: 99%
“…121 Smoking cessation should be encouraged. Immune system diseases such as HIV infection also increase the risks of surgical site infections 130 as do autoimmune diseases such as Rheumatoid Arthritis. 123 These can be managed medically but cannot be eliminated as risk factors.…”
Section: Wound Care and Infection Preventionmentioning
confidence: 99%
“…internal fixation of open tibias was associated with a higher risk of infection; HIV was associated with delayed union; and that HIVpositive patients had a higher rate of pin-tract sepsis with the use of external fixation. 118 However, there are a number of factors limiting the validity of their findings: the presence of confounding factors such as smoking, nutrition, small patient number in all the studies and, probably most importantly, CD4 count.…”
Section: South African Context: Issues To Considermentioning
confidence: 99%
“…117 Harrison et al conducted three studies relevant to this topic: a prospective study of open tibia fractures comparing HIV-positive and -negative patients; a prospective study of internal fracture fixation including cases in open fractures comparing wound infection for HIVpositive and -negative patients; and a prospective study of pin-tract sepsis comparing HIV-positive and -negative patients. 117,118 They found that rates of infection were higher in HIV-positive patients;…”
Section: South African Context: Issues To Considermentioning
confidence: 99%
See 1 more Smart Citation